Thử Tìm Một Biểu Tượng Mới Về Chúa Thánh Thần Cho Giới Trẻ Thời Đại Công Nghệ Số: Attempt to Find a New Symbol for the Holy Spirit for the Young Generation in the Digital Era - Nguyễn, Kế (Khoa Học Công Giáo và Đời Sống, 2023)
Thực tế cho thấy ngôn ngữ là một phạm trù vô cùng rộng lớn chứ không chỉ gói gọn trong lời nói và chữ viết. Có những ngôn ngữ không có âm thanh mà vẫn diễn tả được những thực tại phong phú, ta có thể gọi đó là ngôn ngữ biểu tượng. Cho nên, không lạ gì khi Kinh Thánh trình bày về tính huyền nhiệm trong hoạt động của Chúa Thánh Thần bằng những hình ảnh và biểu tượng hơn là những định nghĩa bằng lời nói hay chữ viết, bởi vì “Gió muốn thổi đâu thì thổi. Không ai biết gió từ đâu đến và sẽ đi đâu” (Ga 3,8). Trong bài viết này, qua những cảm nghiệm thực tế, người viết cố gắng “Thử Tìm Một Biểu Tượng Mới Về Chúa Thánh Thần Cho Giới Trẻ Thời Đại Công Nghệ Số.” In the various correlations of life, language is the means by which humans convey and express ideas. People often immediately think of speech and writing when we talk about language. However, sometimes words and writing do not fully express the meaning of ideas, especially abstract concepts that belong to the supernatural realm, which the human mind finds difficult to grasp and express. Reality shows that language is an incredibly vast domain, not just limited to speech and writing. There are languages that do not have sound but can still express rich realities, which we can call symbolic language. Therefore, it is not surprising that the Bible presents the mystical nature of the Holy Spirit's activity through images and symbols rather than definitions in words or writing because "The wind blows wherever it pleases. You hear its sound, but you cannot tell where it comes from or where it is going" (John 3:8). In this article, through practical experiences, the author tries to "Find a New Symbol for the Holy Spirit for the Young Generation in the Digital Age." It is hoped that what is presented in this article can help someone, especially young people, have a clearer understanding of the presence of the Holy Spirit, feel the impact of the Holy Spirit in life, and thus love and diligently come to Him.